2014
DOI: 10.1371/journal.pone.0111246
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Modification Enhances the Anti-Arrhythmic Properties of Human Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: Background/AimsChronic myocardial infarction (MI) results in the formation of arrhythmogenic substrates, causing lethal ventricular arrhythmia (VA). We aimed to determine whether mesenchymal stem cells (MSCs) carrying a hepatocyte growth factor (HGF) gene modification (HGF-MSCs) decrease the levels of arrhythmogenic substrates and reduce the susceptibility to developing VA compared with unmodified MSCs and PBS in a swine infarction model.MethodsThe left descending anterior artery was balloon-occluded to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Likewise, CXCR4, SDF‐1 and HGF hyperexpression were found to improve homing of MSCs in the peri‐infarct area, attenuate LV remodelling and improve contractility. In addition, intramyocardial injection of HGF‐MSC in infarcted pigs resulted in decreased density of sympathetic nerve endings, better electrical stability of the heart and decreased arrhythmias . Integrin‐linked kinase (ILK) directly interacts with integrin molecules, thereby playing an indispensable role in integrin‐mediated cell adhesion and signalling.…”
Section: Genetic Modification Of Mscsmentioning
confidence: 99%
“…Likewise, CXCR4, SDF‐1 and HGF hyperexpression were found to improve homing of MSCs in the peri‐infarct area, attenuate LV remodelling and improve contractility. In addition, intramyocardial injection of HGF‐MSC in infarcted pigs resulted in decreased density of sympathetic nerve endings, better electrical stability of the heart and decreased arrhythmias . Integrin‐linked kinase (ILK) directly interacts with integrin molecules, thereby playing an indispensable role in integrin‐mediated cell adhesion and signalling.…”
Section: Genetic Modification Of Mscsmentioning
confidence: 99%
“…Many studies have been performed to improve the effectiveness of cardiovascular therapy using a variety of populations, including CSC and cardiomyocyte progenitors genetically engineered using the αMHC promoter [ 26 ]. Although the effects of administering different cell types or growth factors, separately and independently, have been analyzed [ 27 , 28 ], few studies have examined their combined effect [ 29 ]. Here, we explored the combination of cell and gene therapy strategies using MSC genetically modified to overexpress IGF-1 or HGF growth factors as a single treatment in a porcine AMI model.…”
Section: Introductionmentioning
confidence: 99%
“…These stimuli activate the Met pathway, exert strong antiapoptotic effects on cardiomyocytes (18)(19)(20), and induce endothelial cell migration by activating Rac1 (21). A study on a pig model of MI showed that treatment with mesenchymal stem cells with modifications in the HGF gene (HGF-MSCs) increases vascular density and Cx43 expression and induces a lower apoptosis rate and a reduced occurrence of ventricular arrhythmias compared with those induced by treatment with unmodified MSCs (22). Intriguingly, the presence of HGF alone recapitulates most of the effects shown in our research.…”
Section: Discussionmentioning
confidence: 99%